CONN SYNDROME PRESENTING AS CENTRAL RETINAL VEIN OCCLUSION. Issue Volume 14:Issues 1(2020) (2020) - Atik, Alp; Wilson, Dennis; Essex, Rohan W.
Abstract : Purpose: To describe a case of central retinal vein occlusion in a young patient presenting with symptomatic malignant hypertension because of Conn syndrome. Methods: Single interventional case report. Results: A 44-year-old man presented with a 1-day history of headache and vision loss in his right eye on a background of malignant hypertension. He was diagnosed with right central retinal vein occlusion. Further investigation of his malignant hypertension revealed Conn syndrome because of an aldosterone-secreting adenoma in the left adrenal gland. Conclusion: This is the first reported case of Conn syndrome presenting as central retinal vein occlusion. Conn syndrome should be suspected in young patients with central retinal vein occlusion because it is a common cause of hypertension and carries significant cardiovascular risk if left untreated. Abstract : A 44-year-old man presented with a right central retinal vein occlusion and malignant hypertension. Investigations revealed Conn syndrome from an aldosterone-secreting adrenal gland adenoma. Conn syndrome is the most common form of primary aldosteronism, which causes 15% of secondary hypertension. Untreated Conn syndrome is associated with life-threatening cardiovascular complications. It has not previously been described in association with central retinal vein occlusion.